Study of elastoplastic bending of sheet blank of different thickness at its bending taking into account the springing effect - D. I. Chernyavsky; D. D. Chernyavsky (Омский научный вестник)
The work analyzes the process of bending the sheet work piece to obtain shaping of sheet metal parts and profiles. The analysis is carried out on the basis of strength calculations of elastoplastic bending of the metal plate. When pressing such a plate, in practice, a spring effect is observed when the curved blank changes its shape under the influence of residual elastic deformations at the end of the pressing process. To compensate for the spring effect, it is necessary to determine the values of elastic and plastic deformations in the sheet blank. The work considers the method of calculation of these values on the basis of available experimental works. Conclusions have been drawn and practical recommendations can be used in the process of setting process parameters for pressing sheet blanks.